2021
DOI: 10.1186/s40529-021-00329-2
|View full text |Cite
|
Sign up to set email alerts
|

Review: the effect of light on the key pigment compounds of photosensitive etiolated tea plant

Abstract: Background Light is the ultimate energy source of plant photosynthesis, which has an important impact on the growth, development, physiology and biochemistry of tea plant. Photosensitive etiolated tea plant belongs to a kind of colored leaf plant, which is a physiological response to light intensity. Compared with conventional green bud and leaf of tea plant, the accumulation of pigment compounds (chlorophyll and carotenoids, etc.) closely related to a series of reactions of photosynthesis in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…As an important raw material for tea processing, the content and composition of the metabolites in the tender shoots are the decisive factors of tea quality [ 11 ]. The quality-related metabolites in the tender shoots of tea plants mainly include catechins, flavonoids and their glycosides, amino acids, alkaloids, nucleotides, saccharides, and organic acids [ 12 , 13 ]. Catechins, flavonoids and their glycosides, and alkaloids are mainly bitter and astringent, while amino acids, nucleotides, and saccharides are mainly umami and sweet [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an important raw material for tea processing, the content and composition of the metabolites in the tender shoots are the decisive factors of tea quality [ 11 ]. The quality-related metabolites in the tender shoots of tea plants mainly include catechins, flavonoids and their glycosides, amino acids, alkaloids, nucleotides, saccharides, and organic acids [ 12 , 13 ]. Catechins, flavonoids and their glycosides, and alkaloids are mainly bitter and astringent, while amino acids, nucleotides, and saccharides are mainly umami and sweet [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the plant’s age changes the metabolism of the phenols and amino acids in the tea leaves, which is regulated by key genes in their biosynthesis pathways [ 20 ]. Although some effects of plant age on tea quality have been reported, in contrast to the depth of research regarding relevant factors, such as environment and processing [ 13 , 21 , 22 ], research on the influence mechanism of plant age on the metabolites of the tender shoots of tea is seriously lagging. The main reason is that the sample materials from the same tea cultivar but with plants of different ages planted in the same environment and under the same management mode are very difficult to find, which has restricted the exploration of its mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…There have been relatively few studies on the regulation of carotenoids in tea leaves. Similar to the carotenoid regulation in other plants ( Fu et al, 2019 ), it was demonstrated that light also influences the synthesis and accumulation of tea pigments ( Yue, Wang, & Yang, 2021 ). The shading of commonly grown green tea varieties will lead to the increased intensity of green coloration on leaves ( Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 70%
“…Previous studies revealed that shading can promote the accumulation of carotenoids in tea leaves ( Sonobe et al, 2018 , Yue et al, 2021 ), but the underlying regulatory mechanism is still unclear. In this study, shading treatment in tea gardens and dark treatment indoors was applied.…”
Section: Introductionmentioning
confidence: 99%
“…plants prefer weaker light intensity and thus may accumulate more chlorophyll under shaded conditions. In tea plants, chlorophyll and carotenoid synthesis-related genes were downregulated in response to strong light but were upregulated in response to shade or reduced light intensity (Yue et al, 2021). Genes involved in the biosynthesis of chlorophyll in P. fallax Hemsl.…”
Section: Discussionmentioning
confidence: 99%